GaAs/AlGaAs buried channel stripe lasers by single-stage MOCVD on V-grooved substrates - Kim, EK; Kim, TG; Son, CS; Hwang, SM; Kim, Y; Park, YK; Min, SK (KOREAN PHYSICAL SOC, 1998)
A well-defined selective GaAs epilayers were successfully grown on V-grooved GaAs substrates by single-stage atmospheric pressure metalorganic chemical vapor deposition (MOCVD) by supplying carbon tetrabromide (CBr4) and carbon tetrachloride (CCl4). Inside the V-grooves, the selectively grown GaAs epilayers exhibited a triangular and a round shape by supplying CBr4 and CCl4, respectively. By using this single-stage selective epitaxial growth technique, GaAs/AlGaAs buried channel stripe lasers with a GaAs active layer completely embedded in AlGaAs barriers were obtained. Room temperature operation was achieved at a wavelength of 869 nm with threshold currents as low as 43.5 mA (pulsed) and 59.9 mA (CW) for a 250 mu m-long uncoated cavity.
Keywords: CHEMICAL-VAPOR-DEPOSITION; QUANTUM-WIRE STRUCTURES; LATERAL GROWTH-RATE; GAAS; FABRICATION; ARRAY